Comprehensive analysis and critical review of randomized clinical trials on safety profiling of Hydroxychloroquine and Belimumab - Maryam, Zahra; Ahmad , Ausaf (Indian Journal of Pharmacy & Drug Studies, 2023)
Systemic Lupus Erythematosus (SLE), an autoimmune disorder is characterized by multiorgan damage, flares, and heterogeneity in its clinical symptoms. The treatment strategy for this notorious disease focuses on long-term anti-SLE treatment to improve the quality of life, prevent flares, and suppress the immune system. Thus, the chronic use of SLE medicines makes it inevitable to study the safety and tolerability of drugs in large populations. In this comprehensive-analytical study, Hydroxychloroquine (HCQ), which is known for its safe use in SLE, and Belimumab, which is comparatively a novel monoclonal antibody were critically analyzed for their adverse events. We performed the absolute risk, relative risk ratio, and odds ratio analysis after critically scrutinizing the clinical trials for significant adverse effects. HCQ showed major effects on the eye and heart. However, based on the results, HCQ was found to be safer than Belimumab, as a few serious complications were found associated with Belimumab. Our results were found to be as per the previous meta-analysis. This comprehensive review is aimed at analyzing the safety profiles of two widely used drugs for SLE I-e HCQ and Belimumab. We have conducted this review, critical analysis was done to critically analyze the clinical trials, and to gather the information of interest from these trials. Both anti-SLE drugs; HCQ and Belimumab were found to be safe for use against SLE. But comparatively, HCQ showed a safer profile than Belimumab which can be attributed to HCQ’s long-term history of use since 1955. The observation emphasized the researchers for further clinical trials with a more standardized approach, specifically for Belimumab to determine its safety and tolerability in the post-marketing stage.